2011
DOI: 10.1503/cmaj.110448
|View full text |Cite
|
Sign up to set email alerts
|

How important is it to identify avoidable hospital readmissions with certainty?

Abstract: • Readmissions to hospital can occur for clinical, socioeconomic and administrative reasons.• Randomized trials show that readmissions can be reduced.• We know today the approximate percentage of readmissions that are potentially preventable.• Given approximate rates, policy-makers can use confidential feedback, public reporting and payment incentives to reduce readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Figure 3 summarises the numbers and percentages of readmissions assigned to each category, and table 1 gives estimates of the percentage of readmissions in each category subject to mandatory non-payment based on English NHS guidelines. 24 Overall, 17% of emergency readmissions within 30 days would be included in the ‘no payment’ scheme, but there was substantial variation between categories. The most penalised category was A1 (potentially preventable—probable suboptimal care, 49% non-payment), and the least penalised was B2 (unstable deterioration, 9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 summarises the numbers and percentages of readmissions assigned to each category, and table 1 gives estimates of the percentage of readmissions in each category subject to mandatory non-payment based on English NHS guidelines. 24 Overall, 17% of emergency readmissions within 30 days would be included in the ‘no payment’ scheme, but there was substantial variation between categories. The most penalised category was A1 (potentially preventable—probable suboptimal care, 49% non-payment), and the least penalised was B2 (unstable deterioration, 9%).…”
Section: Resultsmentioning
confidence: 99%
“…We were deliberately cautious in our terminology—particularly with regard to preventability—as this is a much debated area in the literature. 24 25 …”
Section: Discussionmentioning
confidence: 99%
“…Studies show hospital readmissions not only occur due to clinical reasons. Lack of coordination and communication within the health care system itself also plays a big role [10].…”
Section: Identification Of the Problemmentioning
confidence: 99%
“…With the penalty metric accounting for socioeconomic factors, CMS will have a reduction in the hospital penalties collected [36]. Through the decrease in penalty collection and an increase in Medicare beneficiaries, CMS may have to charge higher Medicare premiums or provide less benefits to the beneficiaries [37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Section 3025 Losersmentioning
confidence: 99%
“…First, although the research on post-discharge interventions to reduce readmissions remains underdeveloped (Hansen et al 2011), at least three post-discharge interventions have been shown to be effective in clinical trial settings, with absolute reductions in readmissions or post-discharge emergency department use in the 5-10% range (Coleman et al 2006;Jack et al 2009;Naylor et al 1999). Second, the variability in risk-adjusted readmission rates between institutions and regions strongly suggests that some readmissions are preventable (Goldfield 2011, Epstein et al 2011.…”
Section: Preventability Of Readmissions and Other Post-discharge Advementioning
confidence: 99%